PENGHILANGAN POLUTAN ORGANIK DALAM AIR BAKU AIR MINUM (SUNGAI SIAK) DENGAN PROSES BIOFILTER STRUKTUR SARANG TAWON - Budijono, Budijono; Hasbi, M. (Jurnal Perikanan dan Kelautan, 2007)
Recently, raw water pollutions in big cities in Indonesia have become seriousproblems, especially in Pekanbaru, the capital of Riau Province. According to thisreason, it is important to develop appropriate low cost technology to solve thisproblem such as developing pretreatment using biological process such assubmerged biofilter. The present study describes the removal organic matter in theriver of Siak water using submerged biofilter with honeycomb tube plastic media.In this method, the removal efficiency of organic matter were affected byhydraulic retention time of the water in the reactor. The shorter hydraulic retentiontime, the less removal efficiency of organic matter.